Бухгалтерський облік витрат на заходи з охорони праці на підприємстві в умовах пандемії COVID-19 - Якименко-Терещенко, Наталія Василівна; Давидюк, Тетяна Вікторівна; Петрова, Ірина Андріївна (Класичний приватний університет, 2020)
У статті обгрунтовано теоретико-методичні засади механізму обліково відображення витрат підприємства на заходів з охорони праці. Проаналізовано статистичні дані щодо виробничого травматизму, зафіксованого на підприємствах, з деталізацією по областях. Узагальнено порядок відображення в системі бухгалтерському обліку витрат на засоби індивідуального захисту, спецхарчування й обов'язкові медогляди, навчання з питань охорони праці. Запропоновано методику відображення в обліку витрат на захист працівників підприємств від COVID-19. Розроблено форму внутрішнього звіту для відображення обсягу таких витрат, що давсть змогу управлінцям аналізувати динаміку та відхилення фактичних витрат компанії на заходи з охорони праці від запланованих, що сприятиме підвищенню обґрунтованості прийняття управлінських рішень щодо ефективності заходів з охорони праці.

At the current stage of economic development the state supervision and control of organization of labor protection at employers is increasing. The success of the enterprise depends on observance of safety requirementst, workers' health and conditions at the workplace.The task of the head of the company to implement measures for labor protection. Тhese include minimizing the likelihood of injury or illness of employees of enterprises while providing comfort for increased productivity. Certain changes in the organization of labor are also due to the fact that managers have to ensure safe working conditions for employees in connection with the activities in the COVID-19 pandemic, the introduction of restrictive measures in Ukraine. The existing system of accounting for expenditure on occupational safety measures is imperfect, it does not allow to achieve an economic effect per unit cost. The purpose of this study is due to the insufficient level of development of issues of organization and methods of reflection in the accounting of expenses for labor protection measures at domestic enterprises to increase their social responsibility. The purpose of the study is to substantiate the theoretical provisions and develop practical recommendations for improving the accounting of expenditure on occupational safety measures. The article includes the developed theoretical and methodological foundations of the mechanism for reflecting in the accounting of enterprise expenses for labor protection measures. Also, statistical data on industrial injuries at enterprises by regions of Ukraine were analyzed in the article. The procedure for reflecting in the accounting system the costs of personal protective equipment, special meals and mandatory medical examinations, training on labor protection issues was developed. The method of reflection in the accounting of expenses for protection of employees of enterprises from COVID-19 is offered. A form of internal report for displaying such expenses is proposed. It will allow managers to analyse the dynamics and deviations of the company's actual expenses on occupational safety measures from the planned ones. It will also improve the validity of managerial decisions on the effectiveness of occupational safety and health measures.
Accounting of costs for occupational health and safety measures at the enterprise under conditions of the COVID-19 pandemic
Keywords: соціальна звітність; оприбуткування спецодягу; лікувально-профілактичне харчування; навчання; enterprise; labor protection; expenditure on occupational safety measures; accounting; social reporting